PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY DAN GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN PENELITIAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2009 – 2012 (Students' Journal of Accounting and Banking, 2014)
The Research purposes are to examine the Corporate Social Responsibility and Good Corporate Governance effects for company values with agency and stkaeholder’s theory.The subject from this research is Manufacturing Company that active and regularly issuing annual report which related to Corporate Social Responsibility program and Good Corporate Governance mechanism in four years within 2009 – 2012, and obtains 17 manufacturing companies. Whereas the Good Corporate Government divided through four proxies, are managerial ownership, institutional ownership, independent commisioner, and audit comittee. This research is using purposive sampling and documentary methode. After all, the data will be analize using qualitative descriptive. Data was collected through the website of the manufacturing company-related, and through www.idx.co.id.The results shows that CSR has a positive effect, while the four variables related to corporate governance negatively affects the value of the company. This suggests for further research in order to add support in the corporate governance variables and adding the sample to the research subjects.Keywords: Corporate Social Responsibility, Good Corporate Governance, and Company Values